Chemistry for Environmental Scientists - Möller, Detlev (De Gruyter textbook., 2015)
This book focuses on general and fundamental chemistry (including required physics) such as properties and bonding of matter, chemical kinetics and mechanisms, phase and chemical equilibrium, the basic features of air (gases), water (liquids) and soil (solids) and the most important substances and their reactions in the environment. Selected key environmental chemical processes are shortly characterised in the light of multi-component and multiphase chemistry. This books is also useful for chemists who are beginning work on environmental issues.